2022
DOI: 10.1101/2022.07.21.501071
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Highly pathogenic avian influenza H5N1 virus infections in wild red foxes (Vulpes vulpes) show neurotropism and adaptive virus mutations

Abstract: During the 2020-2022 epizootic of highly pathogenic avian influenza virus (HPAI) several infections of mammalian species were reported in Europe. In the Netherlands, HPAI H5N1 virus infections were detected in three wild red foxes (Vulpes vulpes) that were submitted with neurological symptoms between December 2021 and February 2022. Histopathological analysis demonstrated the virus was mainly present in the brain, with limited or no detection in the respiratory tract and other organs. Phylogenetic analysis sho… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 29 publications
3
13
0
1
Order By: Relevance
“…The virus was detected in nine red foxes, three polecats, one otter and one badger. This study confirmed the initial findings in three of the red foxes [ 8 ] by greater numbers of animals and across four species. Higher viral RNA loads were consistently detected in the brains of the animals studied compared to those detected in throat or anal swabs.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The virus was detected in nine red foxes, three polecats, one otter and one badger. This study confirmed the initial findings in three of the red foxes [ 8 ] by greater numbers of animals and across four species. Higher viral RNA loads were consistently detected in the brains of the animals studied compared to those detected in throat or anal swabs.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, virus pathogenesis was studied to identify the potential entry route of the virus, the sites of virus replication, and the associated lesions. Collectively, we showed that: (1) the carnivore viruses were less related to each other than to wild birds; (2) across species, the PB2-E627K mutation associated with mammalian adaptation was found as detected in foxes in the previous study [ 8 ]; (3) the brain of most mammals tested positive for viral RNA whereas limited viral RNA or protein was observed in other organs. We conclude that brain samples are important for reliable detection of the HPAI H5N1 virus in mammals, and therefore must be routinely included besides throat and anal swabs in the surveillance program, and HPAI infections in mammals must be made notifiable to the Veterinary Authority.…”
Section: Introductionmentioning
confidence: 65%
See 3 more Smart Citations